Management of Time Resources in Madrasahs to Increase Work Productivity and Effectiveness: Literature Review - Khanali, Ahmad; Madhakomala, R; Rugaiyah (Educational Journal of Bhayangkara, 2023)
This research is a literature review that aims to understand the practice of managing time resources in Madrasas and the factors that influence it. By collecting data from various sources, this research resulted in a better understanding of the practice of managing time resources in Madrasas, as well as the factors that influence these practices, such as competence, motivation, work environment, and organizational support. This research provides a better understanding for practitioners, especially teachers in Madrasahs, to understand the factors that influence their practice of managing their time resources and develop effective strategies to increase work productivity and effectiveness. Although this research does not produce novelty directly, it provides a strong basis for further research to develop models or strategies that are more effective in managing time resources in Madrasahs. This research is expected to make a positive contribution to the development of time resource management practices in Madrasas.